IEEE Congress on Evolutionary Computation 2010
DOI: 10.1109/cec.2010.5586077
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order functions in aesthetic EC encodings

Abstract: The use of higher-order functions, as a method of abstraction and re-use in EC encodings, has been the subject of relatively little research. In this paper we introduce and give motivation for the ideas of higher-order functions, and describe their general advantages in EC encodings. We implement grammars using higher-order ideas for two problem domains, music and 3D architectural design, and use these grammars in the grammatical evolution paradigm. We demonstrate four advantages of higher-order functions (pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Currying higher order functions, i.e., setting a function argument to a fixed value, allows recursion to be used without having to worry about non terminating recursive calls Yu [53]. McDermott et al [33] incorporated this approach into a CFG. Combining higher order functions and lambda abstraction meant that the problem of connectedness in a generated design was addressed and it also allowed for more modularity, regularity and hierarchy in the resulting designs.…”
Section: Grammars For Architectural Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Currying higher order functions, i.e., setting a function argument to a fixed value, allows recursion to be used without having to worry about non terminating recursive calls Yu [53]. McDermott et al [33] incorporated this approach into a CFG. Combining higher order functions and lambda abstraction meant that the problem of connectedness in a generated design was addressed and it also allowed for more modularity, regularity and hierarchy in the resulting designs.…”
Section: Grammars For Architectural Designmentioning
confidence: 99%
“…McDermott et al [33] and Yu [53] showed that grammars were capable of encoding such qualities through the use of higher-order functions (HOF). Higher-order programming requires that functions can be passed to other functions as arguments (first-class functions) and that anonymous functions can be created (lambda expressions).…”
Section: Higher-order Function Grammarmentioning
confidence: 99%
“…We implement these characteristics using the novel method of higher order functions. See McDermott et al [15] for a more detailed discussion on grammars based on higher order functions . …”
Section: Design Grammarmentioning
confidence: 99%
“…We implement these characteristics using the novel method of higher order functions. Our work in this area is discussed in greater detail in [19]. For structural analysis to be performed on the bridges, a mechanism was required for specifying the loads on the structure.…”
Section: Design Grammarmentioning
confidence: 99%